Marketing Strategy of Bay Tat Farinfarel Cake Home Industry In Batu Panco Village, Curup Utara District Rejang Lebong Regency - Putri, Monicha Adela; Silamat, Eddy; Effendi, Darwan (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This research was conducted in early February 2025 until the end of March 2025. This study aims to: 1. Determine the internal and external factors carried out by the Bay Tat Farinfarel Cake MSME business in Batu Panco Village, Rejang Lebong Regency in increasing sales. 2. Determine the right alternative marketing strategy by the Bay Tat Farinfarel Cake business in Batu Panco Village, North Curup District, Rejang Lebong Regency to increase marketing. Determination of respondents in this study used the judgment sampling method/based on considerations in accordance with the objectives of the study, namely to determine the strengths, weaknesses, opportunities, and threats so that alternative marketing strategies for Bay Tat Farinfarel cakes would be obtained. Where the research respondents were Budiyanto MSME business actors in Batu Panco Village. The methods used in this study were SWOT analysis, IFE analysis, EFE. The results of this study are that the best marketing strategy alternative that can be applied by Mr. Budiyanto in increasing the marketing of bay tat products is S-O (Strengths - Opportunities) as follows: a). Utilizing product quality to increase demand for processed bay tat cake products to meet the great public interest in consuming them. b). Utilizing BPOM processing and hygiene standards to attract public interest in consuming bay tat products